2009
DOI: 10.3136/fstr.15.591
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Fish Oil from Langkawi Island, Malaysia

Abstract: Fish oils extracted from 6 species of marine fin fish caught from Pulau Tuba area, near Langkawi Island, a famous tourism destination in Malaysia, were evaluated for their oxidative stability during storage at both -27 and 4℃. The five fish species were "kerisi" (threadfin breams,sScomberomorus commersoni), "kerapu" (groupers, Cynoglossus lingua), "kembong" (Indian mackerel, Psettodes crumei), "gelama kling" (drum-croaker-jewfish, Pristipomodes typus), and "tinggiri batang" (Spanish mackerels, Scolidon sorrako… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In our study, we found that IIs of oil were significantly different ( P < 0.05) among the different extraction methods (Table ). We observed a lower II than was previously detected in oil from starry butterfish ( Stromateus stellatus ), northern lampfish ( Stenobrachius leucopsarus ), and orange roughy ( Hoplostethus atlanticus ) (87.7–92.3 g of I 100 g −1 of oil) extracted with the industrial method (Endo et al ., ) and in oil obtained from five species of commercially important fish in Malaysia (178.71–190.36 g of I 100 g −1 of oil), extracted with the chemical solvent method (Jaswir et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In our study, we found that IIs of oil were significantly different ( P < 0.05) among the different extraction methods (Table ). We observed a lower II than was previously detected in oil from starry butterfish ( Stromateus stellatus ), northern lampfish ( Stenobrachius leucopsarus ), and orange roughy ( Hoplostethus atlanticus ) (87.7–92.3 g of I 100 g −1 of oil) extracted with the industrial method (Endo et al ., ) and in oil obtained from five species of commercially important fish in Malaysia (178.71–190.36 g of I 100 g −1 of oil), extracted with the chemical solvent method (Jaswir et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the mixed fractions of MUFA-and PUFA-rich fish oil with little amount of SFA could attribute to the less oxidation than the purified PUFA. Jaswir et al (2009) studied the PV and AV for Indian mackerel oil stored up to 3 weeks at 4°C and -27°C. The PV increased from trace value to 2.11 and 0.70 at 4°C and -27°C.…”
Section: Days Of Storagementioning
confidence: 99%